A darkness forged in fire [compact disc, unabridged] - Evans, Chris (Chris R.) (Evans, Chris (Chris R.). Iron elves, 2008)
Konowa Swift Dragon, the disgraced former commander of the Iron Elves regiment, is called back into service for an extremely dangerous mission.